2008
DOI: 10.1097/icb.0b013e318113244a
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography of a Subretinal Granuloma in Simultaneous Visceral and Ocular Larva Migrans

Abstract: OCT imaging may offer a practical means of locating and staging posterior pole lesions due to ocular toxocariasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Our findings are in accordance with other publications. Several authors have shown that Toxocara granuloma is associated with vitreous opacities as a sign of inflammation and may induce vitreous traction, macular edema, and epiretinal membrane formation [5, 6, 7, 8, 9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are in accordance with other publications. Several authors have shown that Toxocara granuloma is associated with vitreous opacities as a sign of inflammation and may induce vitreous traction, macular edema, and epiretinal membrane formation [5, 6, 7, 8, 9].…”
Section: Discussionmentioning
confidence: 99%
“…The response to systemic therapy was assessed using deep range imaging optical coherence tomography (DRI-OCT). To our knowledge there are few reports of DRI-OCT findings in OT and only two presenting this parasitic disease as a granuloma overlying the optic disc [5, 6, 7, 8, 9].…”
Section: Case Reportmentioning
confidence: 99%